2021
DOI: 10.1186/s40643-021-00381-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-binding modules targeting branched polysaccharides: overcoming side-chain recalcitrance in a non-catalytic approach

Abstract: Extensive decoration of backbones is a major factor resulting in resistance of enzymatic conversion in hemicellulose and other branched polysaccharides. Employing debranching enzymes is the main strategy to overcome this kind of recalcitrance at present. A carbohydrate-binding module (CBM) is a contiguous amino acid sequence that can promote the binding of enzymes to various carbohydrates, thereby facilitating enzymatic hydrolysis. According to previous studies, CBMs can be classified into four types based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Moreover, it has been reported that the CBM motif tends to bind carbohydrates, for example, polysaccharides. 58 Therefore, the function of FYGL in activating AMPK may be attributed to its abundant hydroxyl groups in the polysaccharide moieties. 16 The PI3K-AKT−mTOR pathway also plays an important role in regulating skeletal muscle growth, and activation of PI3K/AKT signaling can stimulate protein synthesis and inhibit protein degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that the CBM motif tends to bind carbohydrates, for example, polysaccharides. 58 Therefore, the function of FYGL in activating AMPK may be attributed to its abundant hydroxyl groups in the polysaccharide moieties. 16 The PI3K-AKT−mTOR pathway also plays an important role in regulating skeletal muscle growth, and activation of PI3K/AKT signaling can stimulate protein synthesis and inhibit protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that many reported AMPK activators such as astaxanthin, quercetin, and canagliflozin contain hydroxyl groups, indicating that hydroxyl groups are beneficial to their binding to the CBM-KD interface. Moreover, it has been reported that the CBM motif tends to bind carbohydrates, for example, polysaccharides . Therefore, the function of FYGL in activating AMPK may be attributed to its abundant hydroxyl groups in the polysaccharide moieties …”
Section: Discussionmentioning
confidence: 99%
“…Previous metagenomic analysis has shown that Geobacillus encoded enzymes are associated with the debranching of hemicellulose. Since hemicellulose contains heteropolysaccharides with different side chains, the catabolism of hemicellulose requires various debranching enzymes [ 43 ]. Significant synergistic effects between α-galactosidases and mannosidase have been documented in the degradation of carob gum [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This type of CBM has a slit or cavity on the surface, which can bind to a wide variety of glycans, such as xylans, mannans, galactans and starch (Armenta et al 2017). Type C CBM is a small molecule sugar-bound type (Boraston et al 2004) including family 9, 13, 14, 18, etc, and their binding substrates are limited to monosaccharide, oligosaccharide, or polysaccharide terminal sugar groups (Liu et al 2021). Therefore, the target and speci city for substrate recognition of carbohydrates make CBM a good domain structure for anchoring on the cell wall of plants.…”
Section: Introductionmentioning
confidence: 99%